The Filipino youth and news : a study of news sources, choices, and consumption - RON, GAGALAC (Archīum Ateneo, 2012)
The goal of this research was to determine how the young Filipinos view and use news using various mass communication vehicles. Little is known about the patterns on how they use news media as part of their daily routine and for what specific purposes the